PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI FINANSIAL, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Study Kasus Pada Karyawan Bagian Produksi PT. Gatra Mapan Ngijo, Kecamatan Karangploso, Kabupaten Malang) - Haris Herkutanto; Agus Widarko (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACT This research was conducted at PT. Gatra Mapan Ngijo, Karangploso District, Malang Regency. The purpose of this study is to examine and analyze the influence of leadership style, financial compensation, and work motivation on employee performance. The variables used are leadership style, financial compensation and work motivation as independent variable, employee performance as dependent variable. The sample used by PT. Gatra Mapan Ngijo, Karangploso District, Malang Regency as many as 71 respondents by using survey method. Data collection method used is questionnaire (questionnaire). The analysis used included instrument test, normality test, classical assumption test, multiple regression linear test, hypothesis test and coefficient of determination test using multiple linear regression analysis with SPSS 14.0 for windows software. The result of this research shows that leadership style have an effect on employee performance, financial compensation affect to employee performance, and work motivation does not affect to employee performance in PT. Gatra Mapan Ngijo, Karangploso District, Malang Regency. The influence of leadership style, financial compensation, and work motivation on employee performance together affect the performance of employees of PT. Gatra Mapan Ngijo, Karangploso District, Malang Regency.Keywords: performance, leadership style, financial compensation, workmotivation